The interaction between the Nipah virus nucleocapsid protein and phosphoprotein regulates virus replication - Charlene Ranadheera (Nature Portfolio, 2018)
Abstract Continued outbreaks of Henipaviruses in South Asia and Australia cause severe and lethal disease in both humans and animals. Together, with evidence of human to human transmission for Nipah virus and the lack of preventative or therapeutic measures, its threat to cause a widespread outbreak and its potential for weaponization has increased. In this study we demonstrate how overexpression of the Nipah virus nucleocapsid protein regulates viral polymerase activity and viral RNA production. By overexpressing the Nipah virus nucleocapsid protein in trans viral transcription was inhibited; however, an increase in viral genome synthesis was observed. Together, the bias of polymerase activity towards genome production led to the severe inhibition of viral progeny. We identified two domains within the nucleocapsid protein, which were each independently capable of binding the viral phosphoprotein. Evident by our data, we propose that the nucleocapsid protein’s ability to interact with the phosphoprotein of the polymerase complex causes a change in polymerase activity and subsequent deficiency in viral replication. This study not only provides insights into the dynamics of Henipavirus RNA synthesis and replication, but also provides insight into potential targets for antiviral drug development.